An outbreak of two strains of OXA-48 producing Klebsiella pneumoniae in a teaching hospital. Issue 3 (September 2020) - Lim, F.H.; Modha, D.E.; Collins, E.; Westmoreland, D.; Ashton, C.; Jenkins, D.R.
Summary: OXA-48 producers can be difficult to detect in clinical specimens due to phenotypic low-level resistance to carbapenems. Additionally, low infection rates make clinical specimens poor sentinels for the presence of OXA-48 producers within a healthcare institution. We report an outbreak of OXA-48-producing Klebsiella pneumoniae (OXAKp) that was discovered following culture of OXAKp in a urine specimen from a patient with no known risk factors for acquisition. Widespread screening across medical wards in the trust revealed evidence of transmission across several wards. Samples from 60 patients were positive for OXAKp. Five patients had OXAKp clinical infection, four of whom were treated with ceftazidime/avibactam. Variable number tandem repeat analysis of the OXAKp isolates revealed two predominant strain types clustered around two groups of wards. Infection prevention measures included isolation and cohort nursing of infected and colonized patients, restriction of affected ward areas to new admissions, stringent hand hygiene and use of personal protective equipment. Environmental cleaning of patient areas was carried out using chlorine-releasing disinfectants and hydrogen peroxide vapour. Entire wards were decanted to enable effective cleaning of empty ward areas. The outbreak lasted almost five months and is estimated to have cost around £400 000. During the course of the outbreak, there were five reported prescription and administration incidents related to confusion between ceftazidime and ceftazidime/avibactam. No patient harm resulted from these incidents and the implementation of brand name prescribing for ceftazidime/avibactam prevented further incidents.